WHEN CULTURAL EXPRESSIONS EXPLOITED BY THE RIGHT-WING GROUPS: A COMPARATIVE ANALYSIS BETWEEN THE CASE OF INDONESIA AND GERMANY - Praditya, Yosua (UI Scholars Hub, 2024)
Culture is the expression of life that has been held by society for centuries, but it is possible for it to be hijacked by right-wing groups for their own purposes. Since it is an essential component in the formation of collective identities, it is misappropriated by the group to cultivate its ideology and to fragment social cohesion. The case between Indonesia and Germany has been chosen to analyse the similarities of right-wing characters in exploiting culture, including music, through the lens of Margareth Archer's cultural theory and Ulrich Beck's risk society theory, and later compared using Midlarsky’s extremism perspective. This paper is divided into three sub-chapters of analysis, firstly, when culture, music, and right-wing groups are united. Second, how they have managed to attract and politicise audiences, and finally, how they have built up an 'us' and 'them' mentality. In conclusion, both the Indonesian and German cases show that right-wing groups maintain their numbers and expand their new networks through cultural exploitation, including preaching, and music.